Characterization and Inhibitory Effects of Magnetic Iron Oxide Nanoparticles Synthesized from Plant Extracts on HeLa Cells - Bernard Owusu Asimeng; Emmanuel Nyankson; Johnson Kwame Efavi; Amartey Nii Amarkai; Gloria Pokuaa Manu; Elvis Tiburu (International Journal of Biomaterials)
Magnetic Fe3O4 nanoparticles were synthesized from maize leaves and plantain peels extract mediators. Particles were characterized, and the inhibitory effects were studied on HeLa cells in vitro using cyclic voltammetry (CV). Voltammograms from the CV show that Fe3O4 NPs interaction with HeLa cells affected their electrochemical behavior. The nanoparticles formed with higher Fe3+/Fe2+ molar ratio (2.8 : 1) resulted in smaller crystallite sizes compared to those formed with lower Fe3+/Fe2+ molar ratio (1.4 : 1). The particles with the smallest crystallite size showed higher anodic peak currents, whereas the larger crystallite sizes resulted in lower anodic peak currents. The peak currents relate to cell inhibition and are confirmed by the half-maximum inhibitory concentration (IC50). The findings show that the particles have a different inhibitory mechanism on HeLa cells ion transfer and are promising to be further exploited for cancer treatment.